Atractylenolide I Inhibits Nicotine-Induced Macrophage Pyroptosis and Alleviates Atherogenesis by Suppressing the TLR4/ROS/TXNIP/NLRP3 Pathway - Huan-Huan Li; Xian Liu; Yu-Ping Wang; Xi Xu; Lin Zhu; Wei Zhang; Kun Ren (Metabolites)
Background/Objectives: Studies have shown that Atractylenolide I (AT-I) can exert anti-inflammatory and anti-oxidative effects, protecting against the development of various kinds of cardiovascular diseases. However, whether AT-I prevents nicotine-induced atherogenesis is unknown. This study was designed to explore the effects of AT-I on nicotine-induced macrophage pyroptosis and the progression of atherosclerosis. Methods: RT-qPCR and Western blot were used to detect the mRNA and protein levels of TXNIP and pyroptosis-related factors in THP-1-derived macrophages. ELISA was used to detect the secretion of pro-inflammatory cytokines. Hoechst/PI double-staining assay was used to assess plasma membrane integrity. The ROS assay kit, LDH release assay kit, and caspase-1 activity assay kit were used to detect ROS production, LDH release, and caspase-1 activity. Oil Red O, HE, and Masson staining were used to evaluate lipid accumulation, lesion size, and plaque stability in HFD-fed apoE−/− mice. Results: AT-I treatment significantly decreased pyroptosis-related factors expression, disrupted plasma membrane integrity, and down-regulated pro-inflammatory cytokines secretion, thereby inhibiting nicotine-induced pyroptosis of THP-1-derived macrophages. In addition, AT-I decreased ROS production and the expression of TLR4 and TXNIP. Lentivirus overexpression of TLR4 or TXNIP, or pre-treatment with ROS agonist, mainly reversed the anti-pyroptotic effects of AT-I in nicotine-treated THP-1-derived macrophages. Additionally, administering AT-I to HFD-fed apoE−/− mice markedly decreased nicotine-induced up-regulation of pyroptosis-related proteins in the aortas. Enzymatic methods and ELISA assay suggested that AT-I improved dyslipidemia and inflammation in vivo. Oil Red O, HE, and Masson staining showed that AT-I alleviated lipid accumulation, decreased plaque size, and increased plaque stability. Conclusions: Taken together, AT-I can be regarded as a potential phytomedicine that protects against macrophage pyroptosis and atherosclerosis triggered by nicotine.